How does values-based banking counter unfair terms in consumer contracts and notices in Islamic banks in Malaysia? - Abu Bakar, Noor Mahinar; Mohd Yasin, Norhashimah; Ng, See Teong (Faculty of Management & Muamalah, Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2017)
In July 2017, Bank Negara Malaysia (BNM) in collaboration with Malaysian Islamic finance industry, released a ‘Strategy Paper on Value-based Intermediation (VBI)’. This paper articulates strategies to promote the application of VBI which aims to improve the products and services offered by Islamic banking institutions (IBIs) towards a better facilitation of entrepreneurship, community well-being, sustainable environment and economic growth, without compromising on shareholders’ returns. The VBI is based on SharÊ‘ah, which determines the underlying values, moral compass and priorities in Islamic banks. With the adoption of VBI, IBIs will need to consider the impact of their activities and actions on a wider range of stakeholders, including the financial consumers. The main purpose of this study is to highlight the voice of banking consumers on detriments due to unfair terms in consumer contracts and notices, which is rarely heard by IBIs and BNM. Finding in this study reveals that although BNM has issued a number of standards and guidelines to improve fairness, transparency and governance, but the adoption and enforcement of the standards is highly uneven across the Islamic banks in Malaysia. Using content analysis, this study analyses the impact of values-based banking and governance in solving the problem of unfair contract terms and notices in Islamic banks. Therefore, this paper recommends that IBIs to take the leadership role in advocating values-based banking and governance in ensuring fair treatment, ethical banking and a more socially responsible banking environment to the consumers/community in line with sustainable development goals of SharÊ‘ah. The outcome of this study will be helpful to IBIs in enhancing their branding image and reputation towards facilitating business success over time.